Wnt signaling in the heart fields: Variations on a common theme. Issue 3 (6th January 2016) - Ruiz‐Villalba, Adrián; Hoppler, Stefan; van den Hoff, Maurice J.B.
Abstract : Wnt signaling plays an essential role in development and differentiation. Heart development is initiated with the induction of precardiac mesoderm requiring the tightly and spatially controlled regulation of canonical and noncanonical Wnt signaling pathways. The role of Wnt signaling in subsequent development of the heart fields is to a large extent unclear. We will discuss the role of Wnt signaling in the development of the arterial and venous pole of the heart, highlighting the dual roles of Wnt signaling with respect to its time‐ and dosage‐dependent effects and the balance between the canonical and noncanonical signaling. Canonical signaling appears to be involved in retaining the cardiac precursors in a proliferative and precursor state, whereas noncanonical signaling promotes their differentiation. Thereafter, both canonical and noncanonical signaling regulate specific steps in differentiation of the cardiac compartments. Because heart development is a contiguous, rather than a sequential, process, analyses tend only to show a single timeframe of development. The repetitive alternating and reciprocal effect of canonical and noncanonical signaling is lost when studied in homogenates. Without the simultaneous in vivo visualization of the different Wnt signaling pathways, the mechanism of Wnt signaling in heart development remains elusive. Developmental Dynamics 245:294–306, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: In this review we discuss the role of Wnt signaling in the development of the arterial and venous pole of the heart, highlighting the dual roles of Wnt signaling with respect to its time‐ and dosage‐dependent effects and the balance between the canonical and non‐canonical signaling.